Simultaneous Monitoring of Sweat and Interstitial Fluid Using a Single Wearable Biosensor Platform. Issue 10 (2nd August 2018) - Kim, Jayoung; Sempionatto, Juliane R.; Imani, Somayeh; Hartel, Martin C.; Barfidokht, Abbas; Tang, Guangda; Campbell, Alan S.; Mercier, Patrick P.; Wang, Joseph
Abstract: The development of wearable biosensors for continuous noninvasive monitoring of target biomarkers is limited to assays of a single sampled biofluid. An example of simultaneous noninvasive sampling and analysis of two different biofluids using a single wearable epidermal platform is demonstrated here. The concept is successfully realized through sweat stimulation (via transdermal pilocarpine delivery) at an anode, alongside extraction of interstitial fluid (ISF) at a cathode. The system thus allows on‐demand, controlled sampling of the two epidermal biofluids at the same time, at two physically separate locations (on the same flexible platform) containing different electrochemical biosensors for monitoring the corresponding biomarkers. Such a dual biofluid sampling and analysis concept is implemented using a cost‐effective screen‐printing technique with body‐compliant temporary tattoo materials and conformal wireless readout circuits to enable real‐time measurement of biomarkers in the sampled epidermal biofluids. The performance of the developed wearable device is demonstrated by measuring sweat‐alcohol and ISF‐glucose in human subjects consuming food and alcoholic drinks. The different compositions of sweat and ISF with good correlations of their chemical constituents to their blood levels make the developed platform extremely attractive for enhancing the power and scope of next‐generation noninvasive epidermal biosensing systems. Abstract : A wearable dual iontophoresis tattoo for simultaneous detection of glucose in interstitial fluid‐ISF and alcohol in sweat is reported. A temporary tattoo electrode is used to perform reverse iontophoresis and pilocarpine iontophoretic delivery, simultaneously, to extract ISF‐glucose and sweat‐alcohol after eating and drinking. Variations in the glucose‐ISF and sweat‐alcohol concentrations correlate with the blood glucose and alcohol levels.